ANALISIS RENDAHNYA PARTISIPASI SISWA DALAM KEPENGURUSAN OSIS SEBAGAI PEMBINAAN CIVIC DISPOSITION DI SMA NEGERI 7 KOTA JAMBI - Idha, Riany; Dona Sariani; Salam, Muhammad (Civic Education Perspective Journal, 2023)
Analysis Of Low Student Participation In Osis Management As Civic Disposition Development In Sma Negeri 7 Kota Jambi Abstract: The background of this research is based on the problems that occured in SMA Negeri 7 in Jambi City related to the low participation of students in the management of Student Council, as one of the civic disposition developments in schools. The formulation of the problem in this research are: (1) how is student participation in Student Council management as a civic disposition, (2) what is the factor in the low participation of students in Student Council management at SMA Negeri 7 in Jambi City. The purpose of this study was to find out how student participation in OSIS management is a form of civic disposition development in the school environment and to find out what are the factors causing the low student participation in OSIS management at SMA N 7 Jambi City. This research employed a descriptive qualitative method. In this study, there were core informants and student informants who did not participate in the student council management. The main sources of data were an interview and documentation. The data was analyzed by using the data analysis technique of source triangulation. The findings showed that student participation in Student Council management at SMA Negeri 7 in Jambi City has decreased from previous years. The student council management is dominated by phase or class X students, the low participation of students is in the Social Sciences major. The factors that cause the low participation of students in the management of the Student Council, namely the low interest of students to participate in being the board of the Student Council because students feel they cannot be responsible for carrying out their duties as administrators of the Student Council, inadequate budget funds so that many activities in schools cannot be realized this is a factor causing the low interest of students in the Student Council organization, socialization that has not been maximized by coaches, teachers and old administrators about how the impact is obtained when becoming a member in an organization, and inappropriate recruitment of members by still using a system of appointments based on recommendations by teachers and related parties based on external character factors only. Keywords: Participation, OSIS (Student Council), Students, Civic Disposition.